2008
DOI: 10.2174/138920008785821666
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Xenobiotic-Sensing Nuclear Receptors in Liver Diseases – CAR and PXR-

Abstract: The xenobiotic receptors CAR and PXR constitute two important members of the NR1I nuclear receptor family. They function as sensors of toxic byproducts derived from the endogenous metabolism and of exogenous chemicals, in order to enhance their elimination. They regulate numerous genes which are involved in drug and xenobiotic metabolism, including Phase I (cytochrome P450), Phase II (conjugation catalyzed by sulfotransferases, glucuronosyltransferases and glutathione S-transferases), and transporters (multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 0 publications
0
57
0
Order By: Relevance
“…Kakizaki et al identified the protective effect of inhibition of p38 on I/R-induced liver apoptosis in rats. 35) In deoxycholic acid-induced hepatocyte apoptosis, inhibition of p38 MAPK is one antiapoptotic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Kakizaki et al identified the protective effect of inhibition of p38 on I/R-induced liver apoptosis in rats. 35) In deoxycholic acid-induced hepatocyte apoptosis, inhibition of p38 MAPK is one antiapoptotic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Future efforts in detailed chemical analysis will also be needed to identify the specific chemical constituent(s) responsible for the PXR/CARactivating effects of the whole extract. Overall, with the appreciation that PXR and CAR may serve as potential therapeutic targets (10,11), the discovery of specific herbal medicines and some of their chemical constituents as in vitro modulators of PXR and CAR will provide a basis for targeted pharmacodynamic studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that these receptors play a regulatory role in various physiological and pathophysiological processes, such as lipid metabolism, glucose homeostasis, and inflammatory response (10). Collectively, the available evidence suggests that PXR and CAR may be useful targets for pharmaco-logical intervention in various conditions, including hepatic steatosis, cholestatic liver disease, hyperbilirubinemia, osteoporosis, and inflammatory diseases (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of DMEs and transporters at the transcriptional level is regulated by basal transcription factors as well as the xenobiotic nuclear receptors (NRs), pregnane X receptor (PXR) and constitutive androstane receptor (CAR). The NRs heterodimerize with retinoid X receptor a to bind to the promoter regions of the target genes (Mangelsdorf and Evans, 1995;Tien and Negishi, 2006;Kakizaki et al, 2008;Shen and Kong, 2009;Zordoky and El-Kadi, 2009). The molecular mechanism by which DMEs and transporters are downregulated during inflammation is not fully understood.…”
Section: Introductionmentioning
confidence: 99%